Chapter 7 Socializing Responsibility - Levy, Neil (Oxford University Press, 2018)
There is a near universal consensus that the bearers of moral responsibility are the individuals we identify with proper names. I suggest that if we take the exercise of agency as a guide to the identification of agents, we may find that agents sometimes extend into the world: they may be constituted by several individuals and/or by institutions. These extended agents may be responsible for morally significant outcomes. I argue that institutions or extended agents may also be responsible for the failure of individuals to satisfy the epistemic conditions on moral responsibility. Individuals may believe virtuously but falsely, due to the way in which cues to reliability are socially distributed. I conclude by suggesting that a focus on individual responsibility may have distracted us from the urgent task of reforming the institutional actors responsible for widespread ignorance about morally significant facts.